Consumo, digestibilidade aparente e emissão de metano em novilhos F1 Holandês x Gir suplementados com monensina e/ou virginiamicina - Marcelina Pereira da Fonseca (2012)
This study aimed to evaluate the inclusion of additives monensin, virginiamycin and its association on intake, digestibility and methane emission determined in chamber respirometry, in male cattle, F1 Holstein x Gir. Was used a completely randomized design with four treatments. The treatments were control, monensin, virginiamycin and the association between the two additives. The basal diets were composed of sorghum silage with Tanzania grass and concentrated in proportion 50:50. There was no difference (P>0.05) in nutrient intake. The apparent digestibility coefficients were not affected (P>0.05) by inclusion monensin, virginiamycin and its association. Methane emission was affected (P<0.05) by the use of additives, when expressed in L/d, L/kg DM and L/kg DM digestible. The lowest methane production was obtained with the associated use of the two additives. The use of monensin associated to virginiamycin can be an alternative for cattle during growth and fattening, when working with diets of same proportion of roughage and concentrate based on tropical forage conserved, from the viewpoint of improving the energy efficiency of the diets due to the reduction in methane production.